A Possible Approach for Maintaining Effective Omega-6/ Omega-3 Fatty Acid Ratio from Mixed Vegetable Oils - Haque, MM; Rahman, MN; Alam, MJ; Akter, S (Journal of Environmental Science and Natural Resources, 2017)
Vegetable oil rich in omega-3 and omega-6 fatty acids is an important element in the diet of most transitional countries. The ratio of omega-6 to omega-3 in modern diets is approximately 15:1, whereas ratios of 2:1 to 4:1 have been associated with reduced mortality from cardiovascular disease, suppressed inflammation in patients with rheumatoid arthritis, and decreased risk of breast cancer. The study was designed to investigate the fatty acid profile of six types of seed oils such as peanut, linseed, olive, soybean, sesame and sunflower oil. Afterwards the author prepared mixed vegetable oils with effective Omega-6 (n-6)/omega-3 (n-3) fatty acid ratio. It was found that the highest percentage (39.9%) of saturated fatty acid found in Linseed oil and the highest percentage (37.1%) of monounsaturated fatty acid found in Sesame oil. It was also observed that olive and soybean oil contain 100% polyunsaturated fatty acid and the lowest percentages (35.2%) of polyunsaturated fatty acid were found in Sesame oil. After preparing a mixed vegetable oil The ratio of n-6 to n-3 were 3.5:1 (soybean), 19:1 (olive), 0.43:1 (linseed), 0.13:1 (peanut) and sesame (16.5:1). It is also noted that n-3 was not detected in sunflower oil. Thus the investigation showed that Soybean oil contains the balanced omega-6/omega-3 fatty acid ratio than others. J. Environ. Sci. & Natural Resources, 9(2): 65-69 2016